The new Black Evangelicals - Potter, Ronald Clifton (Review and expositor, 2020)
A republication of an article originally included in the 1979 volume, Black Theology: A Documentary History, edited by Gayraud Wilmore and James Cone, this article is an examination of the emergence of a radical Black Evangelicalism within the National Association of Black Evangelicals in the late 1960s and early 1970s. It demonstrates the ways in which Black contributions are often forgotten and marginalized.